HİPEROKSALÜRİNİN MESANE EPİTELİ ÜZERİNDE MEYDANA GETİRDİĞİ HASAR VE BU HASARIN LOSARTAN TARAFINDAN GERİ DÖNDÜRÜLMESİ - TUNÇ, Burçin; DEMİRKESEN, Oktay; UYANER, İlhan; GÜREL, Ebru; KAPUCU, Ayşegül; TURAN, Tahir (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Hyperoxaluria is a recognized cause of tubulointerstitial lesions in the kidney and it may contribute to chronic renal failure. Although the mechanism could not be well understood, in previous studies it was demonstrated that angiotensin II type I receptor blocker losartan was effective against the progression of tubulointerstitial lesions caused by hyperoxaluria. As far as we know, up to date the effects of hyperoxaluria on bladder were not studied although hyperoxaluric urine is stored in the bladder. In this study we tried to evaluate the damage of hyperoxaluria on bladder and epithelium, and action of losartan on these lesions: Two-month-old male Sprague-Dawley rats were randomized into four groups according to drinking water, 1-control animals given tap water only (n: 10 rats), 2-animals made hyperoxaluric by adding 1% ethylene glycol to the drinking water (n: 10 rats), 3-animals that were fed with 1% ethylene glycol plus 20 mgr/l angiotensin II type I receptor blocker losartan (n:10 rats), 4-animals fed with only losartan (n: 10 rats). In metabolic cages at the beginning and after four weeks, urine of the rats was collected for twenty-four hours and creatinine clearance, urinary albumin excretion, urinary pH and urinary oxalate levels were determined. Results were compared with the beginning levels and within the groups. Kruskal Wallis, ANOVA and Wilcoxan Rank probability tests were used as statistical methods and p<0.05 were considered as significant. Results.- There was no difference in urine oxalate excretion in ethylene glycol and ethylene glycol and losartan group. Renal functions significantly worsened in ethylene glycol group when compared with ethylene glycol and losartan group. Urine pH and nitrate levels were similar among the groups. Histological examination of the bladders revealed that in the second group, there were increased intracytoplasmic vacuolisation in the epithelium, epitheliums’ heights were also increased and in the connecting tissue there were increased bleeding points. Although some bleeding points in the connective tissue were seen in the third group, these were recovered by organization and there was increased mitosis at the connective tissue. Bladder’s height was decreased compared to group 1 and intrasitoplasmic vacuolization was not seen in this group. Bladder specimens had similar properties in control group and losartan group. Conclusion.- In this study we showed that hyperoxaluria causes epithelial damage in the bladder as in the tubulointerstitium. Losartan reverses this damage by increasing mitosis and prevents bladder epithelium. At this moment we do not know the relation between our hystochemical and hystologic result and clinical symptoms. Further investigations are needed on this subject.